Comparison of Clinical Competency in Nurses Working in Covid-19 and non-Covid-19 Departments of University Hospitals in Zanjan City in 2020 - Masomeh Ahmadi; Mojghan Sadat Aghvamy; Zeinab Gahremani (Zanjan University of Medical Sciences and Health Services, 2022)
Background: The importance of clinical competency in nurses indicates the necessity of evaluating this criterion for nurses working in Covid-19 and non-Covid-19 departments. Objectives: Comparison of clinical competency in nurses working in Covid-19 and non-Covid-19 departments of university hospitals in Zanjan city in 2020. Methods: Following a convenient sampling method, this cross-sectional study recruited 220 registered nurses working at hospitals affiliated to the Zanjan University of Medical Sciences with at least six months of work experience. Data were collected using a demographic information form and competency inventory for registered nurses (CIRN). Mann Whitney U test was used to compare study groups. Results: There was a significant difference between nurses working in Covid-19 and non-Covid-19 departments concerning clinical competency, so that those in Covid-19 departments were more competent (p-value=0.001). Conclusion: The observed difference requires more attention and particular interventions, including promoting teamwork, engaging staff in decision-making processes, job supports, reducing conflicts and role ambiguities, and increasing control over employment-related events.